Geomorphology and the natural hazard of Huong coastal estuaries - Quan, Nguyen Cong; Hung, Pham Van (Vietnam Journal of Marine Science and Technology, 2019)
The geomorphological features and related geological hazards of the estuarine and coastal area of the Huong river are concluded from latest synthetic data. The estuarine terrain of Huong river was the result of interaction amongst neo and modern tectonic activities with exogenic dynamic factors as marine, marine - fluvial and fluvial. The estuary of Huong river is placed on the northwest - southeast neo - modern tectonic Quang Dien - Phu Vang depressed plate which has 3 local depressed blocks where then were filled by marine, marine - fluvial and fluvial sediment. The marine sediment was mostly distributed on the northwestern and southeastern blocks while the central block was mostly filled by marine - fluvial sediment. The terrain of coastal and estuarine area of Huong river had 18 types, they have changed dramatically within spatial and sequential dimension for those periods: Pliocene - early Pleistocene, middle - late Pleistocene, early - middle Holocene and late - modern Holocene. During Pliocene - early Pleistocene and middle-late Pleistocene, weak uplifting movement to the north of the area had created the denudation surfaces, erosion and abrasion terraces with heights over 20 m, whereas the depressed area to the east had been filled by several hundred meters of fluvial and fluvial - marine sediment. In the early - middle Holocene, depressing movement and retrogradation caused the marine and fluvial - marine sediment accumulated rapidly up to tens of meters. In the last phase of late-modern Holocene, weak depressing combined with moderate uplifting movement happenned, hence the accumulation of fluvial, fluvial - marine - marsh sediments. The shoreline of studied area had changed dramatically in the modern Holocene. In the early-middle Holocene, the shoreline was about 20 km inland of Quang Dien - Inner Citadel area and about 15 km of Phu Vang area. The strong morphodynamic process occured and caused erosion - accretion of the coastal estuarine of Huong river, and changed the modern shoreline locations. At Thuan An inlet, erosion happened by the foot of coastal dunes at the rate of 6.4 m annually; but there was only accretion in Hai Duong coast. The bank of Huong river was also eroded, especially from Tuan junction to Tam Giang lagoon, and the most seriously erosion locations area La Khe commune, Bang Lang - Thuy Bang, Long Ho - Xuoc Du, Thien Mu pagoda and Dia Linh - Huong Vinh.